Prevalence of Clostridium difficile and Multidrug Resistant Gram-negative Rods in the Soil from Southeastern Wisconsin. (4th October 2017) - Lor, Angela; Tran, Cathy; Jencson, Annette; Cadnum, Jennifer; Donskey, Curtis; Munoz-Price, L Silvia
Abstract: Background: Preliminary data suggests that community-onset Clostridium difficile might be more common in rural areas. Thus, farms—specifically livestock farms—might be a major reservoir of C. difficile . Similarly, antibiotic exposures might predispose farm animals for colonization with multidrug resistant Gram-negative organisms. The aim of this study was to determine the prevalence of C. difficile and multidrug resistant gram-negative rods in the soil of Southeastern Wisconsin farms. Methods: From July to September of 2016, soil samples were collected from farms with livestock animals. Soil samples were collected using gloves and sample containers. Soil samples were collected from farms specifically in or near Washington, Waukesha, and Milwaukee counties which are within the proximity of Milwaukee Metro area. Soil samples were cultured for C. difficile and Gram-negative rods on selective plates and by broth enrichment. Results: A total of 20 farms participated in this study with a total of 40 soil samples. Out of the 40 soil samples, 20 were from an area where animals roam or where manure was used and the remaining 20 were from an area where animals are prohibited or where there was no manure. Out of the 20 soil samples where animals roam, 10 (50%), tested positive for C. difficile. Out of 20 soil samples where animals are prohibited, 13 samples (65%) tested positive for C. difficile . 2 of the 23 C. difficile isolates recovered were toxigenic. Eight (40%) of the 20 soil samples where animals roam tested positive for fluoroquinolone-resistant bacteria (FQR). While 5 (25%) of the 20 soil samples where animals are prohibited, tested positive for FQR bacteria. An Acinetobacter calcoaceticus was found to exhibit carbapenem-resistance. Conclusion: We found soil colonization with C. difficile and FQR in 65% and 25%, respectively, where animals are prohibited. Where animals roam we found C. difficile and FQR 50% and 40%, respectively. Our study suggests that farms may be a significant community source for C. difficile and fluoroquinolone resistant organisms. Additional testing should be done to examine factors that might be increasing antibiotic resistance in farms (e.g., antibiotic exposure). Disclosures: All authors: No reported disclosures.